Validitas dan reliabilitas angket gaya belajar VAK (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to test the validity and reliability of the VAK learning style questionnaire. The population of this study were all mathematics education students at the Universitas PGRI Semarang. The research sample consisted of 114 students who were taken by simple random sampling. The data collection technique was carried out using an adaptation of the VAK learning style questionnaire developed by Victoria Chislett & Alan Chapman. Data analysis techniques include validity test using the Karl Pearson’s Product Moment correlation and reliability test using the Cronbach’s Alpha. The results of this study indicate that the adaptation of the VAK learning style questionnaire developed by Victoria Chislett & Alan Chapman in Indonesian is very good, because it fulfills valid and reliable criteria, so that the questionnaire can be used to identify a person's learning style.
Keywords: learning style; reliability; questionnaire; VAK; validity